Analysis Of Midwife's Knowledge In Early Management Practices In Peb Cases At Karunia Kasih Pondok Gede Hospital In 2023 - Siska Prasetia Utami; Feva Tridiyawati; Budi Ermanto; Udur Diana Tumanggor (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
According to WHO the Maternal Mortality Rate (MMR) is very high. About 287,000 women died during and after pregnancy and childbirth. The causes of AKI were eclampsia (37.1%), bleeding (27.3%), infection (10.4%). Analyzing the knowledge of midwives in initial management practices in PEB cases at Karunia Kasih Hospital Pondok Gede in 2023.Using qualitative with Rapid Assessment Procedures (RAP) design. The study population was midwives who worked at RS Karunia Kasih Pondok Gede as many as 10 respondents. The research sample used a total sampling of 10 respondents. bivariate analysts use uji Chi-square.The majority of midwives who are knowledgeable enough are as many as 5 respondents (50%), well knowledgeable as many as 3 respondents (30%) and those with less knowledge as many as 2 respondents (20%).Obtained analysis of midwives' knowledge in the initial management practice in PEB cases at RS Karunia Kasih Pondok Gede, the average midwife is sufficiently knowledgeable. Suggested in this study for educational institutions, for research sites, for respondents and for future researchers.